NLGN4X TCR transgenic T cells to treat gliomas - Krämer, Christopher; Kilian, Michael; Chih, Yu-Chan; Kourtesakis, Alexandros; Hoffmann, Dirk C.; Boschert, Tamara; Koopmann, Philipp; Sanghvi, Khwab; De Roia, Alice; Jung, Stefanie; Jähne, Kristine; Day, Bryan; et al. (Neuro-Oncology, 2024)
Background.   Neuroligin 4 X-linked (NLGN4X) harbors a human leukocyte antigen (HLA)-A*02-restricted tumorassociated antigen, overexpressed in human gliomas, that was found to induce specific cytotoxic T cell responses following multi-peptide vaccination in patients with newly diagnosed glioblastoma. - Methods.   T cell receptor (TCR) discovery was performed using droplet-based single-cell TCR sequencing of NLGN4X-tetramer-sorted T cells postvaccination. The identified TCR was delivered to Jurkat T cells and primary human T cells (NLGN4X-TCR-T). Functional profiling of NLGN4X-TCR-T was performed by flow cytometry and cytotoxicity assays.Therapeutic efficacy of intracerebroventricular NLGN4X-TCR-T was assessed in NOD scid gamma (NSG) major histocompatibility complex (MHC) I/II knockout (KO) (NSG MHC I/II KO) mice bearing NLGN4Xexpressing experimental gliomas. - Results.   An HLA-A*02-restricted vaccine-induced T cell receptor specifically binding NLGN4X131-139 was applied for preclinical therapeutic use. Reactivity, cytotoxicity, and polyfunctionality of this NLGN4X-specificTCR are demonstrated in various cellular models. Intracerebroventricular administration of NLGN4X-TCR-T prolongs survival and leads to an objective response rate of 44.4% in experimental glioma-bearing NSG MHC I/II KO mice compared to 0.0% in control groups. - Conclusion.   NLGN4X-TCR-T demonstrate efficacy in a preclinical glioblastoma model. On a global scale, we provide the first evidence for the therapeutic retrieval of vaccine-induced human TCRs for the off-the-shelf treatment of glioblastoma patients.Keywords cell therapy | glioblastoma | T cell receptor | tumor antigen
Online veröffentlicht: 16. September 2023
Gesehen am 08.01.2024